THE INFLUENCE OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, AND ATTITUDE TOWARD BEHAVIOR ON THE INTENTION TO USE OF INTERNET BANKING (Case Study at BNI 46 Bank Kln Brawijaya University Malang) - Rizky Januarsyah (Jurnal Administrasi Bisnis, 2015)
This research aims to determine the influence of ease of use, usefulness, and attitude of the users in the use of of Internet Banking. This research intended for costumers who use Internet Banking in banking activities, are classified in several categories including age and gender. This research is based on two theories, that is Theory of Reasoned Action (TRA) and Technology Acceptence Model (TAM). This research uses quantitative methods using questionaire to obtain data to be processed, the researcher collected the data in BNI 46 Bank KLN Brawijaya Universitas Malang with the and customers who use internet banking as a sample. The results of this research are two of the three factors giving influence to the user in the use of Internet Banking.  Keywords: Internet Banking, Influence of TAM and TRA, Bank. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh kemudahan penggunaan, kegunaan, dan sikap pengguna dalam penggunaan Internet Banking. Penelitian ini ditujukan untuk pelanggan yang menggunakan Internet Banking di dalam kegiatan perbankan, diklasifikasikan dalam beberapa kategori termasuk usia dan jenis kelamin. Penelitian ini didasarkan pada dua teori, yaitu Theory of Reasoned Action (TRA) dan Technology Accaptance Model (TAM). Penelitian ini menggunakan metode kuantitatif dengan menggunakan kuesioner untuk mendapatkan data yang akan diproses, peneliti mengumpulkan data di BNI 46 Bank KLN Universitas Brawijaya Malang dan nasabah yang menggunakan internet banking sebagai sampelnya. Hasil penelitian ini adalah dua dari tiga faktor yang memberikan pengaruh kepada pengguna dalam penggunaan Internet Banking. Kata kunci: Internet Banking, Influence of TAM and TRA, Bank.